THE IMPACT OF PSAK 73 IMPLEMENTATION ON LEASES IN INDONESIA TELECOMMUNICATION COMPANIES - Hendri Josep Saing; Amrie Firmansyah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study investigates the impact of PSAK 73 implementation regarding Leases by Telecommunications Companies in Indonesia. This study employs a qualitative approach with content analysis. The basis of content analysis in this study is data and information sourced from the company's audited financial statements. The employed data is secondary data in companies' financial statements in the telecommunications sub-sector in 2019 and 2020, sourced from www.idx.co.id. Based on the availability of data, the sample employed in this study consists of 4 companies. This study concludes that the PSAK 73 implementation impacts an increase in asset and liability items. The increase in debt to asset ratio, debt to equity ratio can increase the cost of capital borne by the company, although on the other hand, the return on assets and the return on equity have increased. This study indicates that the companies need to mitigate the risks associated with implementing the newly enacted financial accounting standards. In addition, this study indicates that the Indonesian Chartered Accountants should consider the risks borne by companies related to the implementation of financial accounting standards in Indonesia.